LOOKING ON THE BRIGHT SIDE OF GRAMMAR-TRANSLATION METHOD - Zulprianto - - (Universitas Katolik Indonesia Atma Jaya, 2012)
In spite of having been rejected as a method in language teaching, the Grammar-Translation Method (GTM) has never been totally left out. Among the rejections to the GTM are because the language learners’ native language is used as the medium of instruction and the grammar is taught deductively. However, GTM is composed of two features hardly inescapable in any discussion about language teaching: grammar and translation. If grammar serves as a medium to know about the form of language, translation can interlingually guide the way to comprehending the meaning of language. This article is aimed to explain the importance of grammar and translation in language teaching and to propose some modifications of the ways in which both can be taught that can possibly restorethe bright side of the GTM to some extent.Keywords: Grammar-Translation Method (GTM), grammar,translation